PENGARUH INSENTIF PAJAK, LEVERAGE, UKURAN PERUSAHAAN DAN PROFITABILITAS TERHADAP KONSERVATISME AKUNTANSI DI BURSA EFEK INDONESIA TAHUN 2017-2020 - Yolanda, Herlina; safiq, muhamad (Jurnal Riset Akuntansi Soedirman, 2024)
This study aims to examine the influence of tax incentives, leverage, company size, and profitability on accounting conservatism. The technique used in this research is quantitative method and purposive sampling. The data used in this study are secondary data in the form of financial statements of the company from the site of the Indonesia Stock Exchange in the years 2017-2020. for the data analysis used is a multiple linear regression analysis using the tools of SPSS version 25. The results of the analysis of this study are (1) tax incentives have a significant effect on accounting conservatism. (2) leverage has a significant effect on accounting conservatism. (3) the size of the company has a significant effect on accounting conservatism. (4) profitability has no significant effect on accounting conservatism. Furthermore, tax incentives, leverage, company size, and profitability together affect accounting conservatism significantly.